2021
DOI: 10.1186/s12885-021-08087-x
|View full text |Cite
|
Sign up to set email alerts
|

Are socio-economic inequalities in breast cancer survival explained by peri-diagnostic factors?

Abstract: Background Patients living in more deprived localities have lower cancer survival in England, but the role of individual health status at diagnosis and the utilisation of primary health care in explaining these differentials has not been widely considered. We set out to evaluate whether pre-existing individual health status at diagnosis and primary care consultation history (peri-diagnostic factors) could explain socio-economic differentials in survival amongst women diagnosed with breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Research has shown that cancer awareness, clinical (comorbidities) and tumour-related (tumour stage) factors can only explain part of the inequalities in England [ 18 20 ] and that more emphasis should be given to the observed variation in cancer screening uptake [ 21 23 ] and management of patients [ 24 26 ]. However, communication of these epidemiological findings with political forces and stakeholders has been suboptimal, evidenced by the lack of initiative to target inequalities in a more methodical fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that cancer awareness, clinical (comorbidities) and tumour-related (tumour stage) factors can only explain part of the inequalities in England [ 18 20 ] and that more emphasis should be given to the observed variation in cancer screening uptake [ 21 23 ] and management of patients [ 24 26 ]. However, communication of these epidemiological findings with political forces and stakeholders has been suboptimal, evidenced by the lack of initiative to target inequalities in a more methodical fashion.…”
Section: Introductionmentioning
confidence: 99%
“…The literature in this area is inconclusive, with some previous research suggesting that presentation with cancer-alarm symptoms is not necessarily correlated with socioeconomic status and others suggesting lower socioeconomic status can be linked to delayed presentation. 15,16 Our findings suggest referrals to the pathway are affected in similar ways to other cancer pathways; however, a larger sample size is needed to study effects on time to diagnosis and treatment outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, another study in Germany revealed significantly excess cancer-related avoidable mortality in the more deprived regions [24]. Deprivation was also positively associated with breast cancer survival in England, in which each unit increase in deprivation quintile was associated with an increase in excess mortality [25]. The results of our study make a significant contribution to the existing literature because our data obtained from the general population show that area deprivation levels may also be associated with cancer-related avoidable deaths in Korea.…”
Section: Discussionmentioning
confidence: 83%